Towards a core approach for cross-sectional farm household survey data collection: a tiered setup for quantifying key farm and livelihood indicators - CGIAR Research Program on Wheat (2019)
report with contributions by : ILRI; ICRISAT ; Bioversity International; IFPRI ; CIAT; University of Naples; Evans School of Public Policy and Governance, University of Washington; CGIAR-ISPC; IRRI; Worldfish; KIT; Oregon State University; Wageningen University; CIMMYT; FAO; IFAD.